Student Aspiration Processing Information System with Sentiment Analysis at Piksi Ganesha Polytechnic - Maulidia Tuzahra; Johni S Pasaribu (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
Student aspirations play an important role as a means of two-way communication to improve the quality of academic and non-academic services in higher education. However, manual aspiration submission systems often result in delays in follow-up and a lack of documentation. This study aims to design and implement a web-based student aspiration processing information system integrated with sentiment analysis. The development method used is Waterfall, with stages of requirements analysis, design, implementation, testing, and maintenance. The implementation was carried out using the PHP programming language and MySQL database. The main features of the system include registration, login, feedback form, feedback list, admin replies, and lexicon-based sentiment analysis. Testing using Black Box Testing showed that all functions ran according to user requirements (100% success rate), with an average system response time of 2.7 seconds and a user satisfaction rate of 92%. This system is capable of classifying aspirations into positive (46%), negative (38%), and neutral (16%) categories, thereby facilitating the evaluation of campus services. This research proves that the system is capable of accelerating the handling of aspirations by up to 40% compared to manual mechanisms and supports decision-making based on sentiment data.